2006
DOI: 10.1159/000097105
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oral Cefatrizine in Pregnant and Non-Pregnant Women with Reference to Fetal Distribution

Abstract: Objective: To investigate the effect of gestation on the pharmacokinetics of orally administered β-lactams, choosing cefatrizine as the model antibiotic. Setting: A tertiary teaching hospital. Design: Prospective study. Methods: In 20 women with affected fetuses, 17 by β-thalassemia major and 3 with congenital malformations, termination of gestation between 19 and 24 weeks was induced by intra-amniotic administration of prostaglandin F2α. Pharmacokinetics of cefatrizine in maternal and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The scope of studies to investigate both PK and clinical outcome data seems to be dependent on drug class. For example, none of the studies that investigated antibiotics [47,52,53] or anesthetic and analgesic drugs [102] provided data on clinical outcomes. On the other hand, studies of addiction management drugs and antidepressant drugs reported clinical data, showing a positive correlation between decreased drug exposure and diminished clinical effects in pregnancy [70,202].…”
Section: Discussionmentioning
confidence: 99%
“…The scope of studies to investigate both PK and clinical outcome data seems to be dependent on drug class. For example, none of the studies that investigated antibiotics [47,52,53] or anesthetic and analgesic drugs [102] provided data on clinical outcomes. On the other hand, studies of addiction management drugs and antidepressant drugs reported clinical data, showing a positive correlation between decreased drug exposure and diminished clinical effects in pregnancy [70,202].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cefatrizine, a cephalosporin antibiotic, is eliminated by renal mechanisms and not metabolized. Pregnancy reduces the antibiotic's oral availability by 43%, serum concentration by 45%, and extends its elimination half-life by one hour [7]. …”
Section: Introductionmentioning
confidence: 99%
“…A substantial decrease was observed in AUC 0−12h and C max (43 and 44%, respectively) in pregnant women compared to that in nonpregnant women. Furthermore, a 1.63-fold (2.48 vs 1.52 h) increase was observed in the half-life of the drug in pregnant women (Papantoniou et al, 2007).…”
Section: Pregnancymentioning
confidence: 90%
“…42 Cefatrizine serum concentrations (mean ± SD, μg/mL) in 20 female volunteers (circles) and 20 women in the 23rd week of gestation (squares) after the administration of the third oral dose of 1 g cefatrizine every 12 h. Source: Reproduced fromPapantoniou et al (2007) with permission.…”
mentioning
confidence: 99%